2021
DOI: 10.34119/bjhrv4n1-082
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of drug interactions and their impact on virological failure of people living with HIV/AIDS over 50 years of age / Avaliação das interações medicamentosas e seu impacto no fracasso virológico de pessoas vivendo com HIV/AIDS acima de 50 anos de idade

Abstract: The discovery of the antiretroviral therapy (ART) increased life expectancy of people living with HIV (PLHIV). This chronic condition was associated with other diseases with a higher risk of multiple drug use and drug interactions. Drug interactions can cause therapy failures and side effects. This cross-sectional study was carried out in three specialized clinics located in the northwestern of the state of São Paulo from September to December 2019, and evaluated the potential drug interactions in PLHIV and it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 27 publications
(36 reference statements)
0
0
1
Order By: Relevance
“…Among the twenty-nine participants identified in hyperpolypharmacy for this study, sociodemographic, clinical, life habits, functional ability characteristics and drug interaction data were analysed. The prevalence of major and moderate interactions was higher than those observed by Leite et al [8] in a Primary Care Service but lower than in HIV patients [9]. The results revealed that certain characteristics were associated with minor, moderate, and/or major drug interactions more frequently than other characteristics.…”
Section: Discussioncontrasting
confidence: 55%
“…Among the twenty-nine participants identified in hyperpolypharmacy for this study, sociodemographic, clinical, life habits, functional ability characteristics and drug interaction data were analysed. The prevalence of major and moderate interactions was higher than those observed by Leite et al [8] in a Primary Care Service but lower than in HIV patients [9]. The results revealed that certain characteristics were associated with minor, moderate, and/or major drug interactions more frequently than other characteristics.…”
Section: Discussioncontrasting
confidence: 55%